NEGARA KESEJAHTERAAN (WELFARE STATE) DALAM PANDANGAN ISLAM DAN KAPITALISME - Ariza Fuadi (Universitas Alma Ata, 2015)
Abstract Etimologically, the term of welfare state consists of two words welfare and state. Welfare means prosperity or safety, and state is deﬁ ned as an agency of the society that having a power to control the relation of people and produce the symptoms of power within the society. The term of welfare state is often called in bahasa as negara kesejahteraan. The term of welfare state was used in English by Archbishop York from UK in 1940 as the response and resistance of warfare state from Nazi Hitler in Germany. Welfare state was conducted ﬁ rstly in Europe and US. This program has been conducted to improve the economic system of capitalism more compassionate and to protect the weak within the society as the result of “wickedness” of capitalism. However, the program of welfare state, as time goes by, that has been conducted by capitalism has not worked to create prosperity for the people. The poverty and injustice are still happening until now. These are happening since the misleading of capitalism that only focuses on the increase economic development towards the existence of state creating social prosperity within the society. Therefore, besides material development, Islamic welfare state also focuses on the moral material aspect without followed by spiritual uplift. It is different from Islamic welfare state that gives the interrelated comprehensive concept. This linkage consists of the roles of state and religion to aspect as a social control for the human prosperity. Keywords: Welfare State, Capitalism, Islam